Advances in the Spectral Index method for the analysis of photonic integrated circuits - Greedy, Stephen (2002)
The prolific rate at which advances in photonics have been made in recent years has increased the need for accurate and efficient computer aided design tools. New device technologies and material systems mean the designer is faced with many more degrees of freedom with which to optimise a design. Because of this versatile techniques that yield results accurately and quickly are foremost in the designers mind.